Future Directions for the National Science Foundation's Arctic Natural Sciences Program - National Research Council (The National Academies Press, 1998)
Keywords: Earth Sciences; Transportation and Infrastructure

Teaching About Evolution and the Nature of Science - National Academy of Sciences (The National Academies Press, 1998)
Today many school students are shielded from one of the most important concepts in modern science: evolution. In engaging and conversational style, Teaching About Evolution and the Nature of Science provides a well-structured framework for understanding and teaching evolution. Written for teachers, parents, and community officials as well as scientists and educators, this book describes how evolution reveals both the great diversity and similarity among the Earth's organisms; it explores how scientists approach the question of evolution; and it illustrates the nature of science as a way of knowing about the natural world. In addition, the book provides answers to frequently asked questions to help readers understand many of the issues and misconceptions about evolution. The book includes sample activities for teaching about evolution and the nature of science. For example, the book includes activities that investigate fossil footprints and population growth that teachers of science can use to introduce principles of evolution. Background information, materials, and step-by-step presentations are provided for each activity. In addition, this volume: Presents the evidence for evolution, including how evolution can be observed today. Explains the nature of science through a variety of examples. Describes how science differs from other human endeavors and why evolution is one of the best avenues for helping students understand this distinction. Answers frequently asked questions about evolution. Teaching About Evolution and the Nature of Science builds on the 1996 National Science Education Standards released by the National Research Council—and offers detailed guidance on how to evaluate and choose instructional materials that support the standards. Comprehensive and practical, this book brings one of today's educational challenges into focus in a balanced and reasoned discussion. It will be of special interest to teachers of science, school administrators, and interested members of the community.
Keywords: Education; Biology and Life Sciences

Learning About Assessment, Learning Through Assessment - National Research Council (The National Academies Press, 1998)
The MSEB, with generous support and encouragement from the Carnegie Corporation of New York, seeks to bring discussion of assessment to school-and district-based practitioners through an initiative called Assessment in Practice (AIP). Originally conceived as a series of "next steps" to follow the publication of Measuring Up and For Good Measure, the project, with assistance from an advisory board, developed a publication agenda to provide support to teachers and others directly involved with the teaching and assessment of children in mathematics classrooms at the elementary, middle, and high school levels. In a series of three booklets, AIP presents an exploration of issues in assessment. The first booklet, Learning About Assessment, Learning Through Assessment discusses ways to assist teachers in learning about assessment and how student work can be a rich resource in professional development. The second, Assessment in Support of Instruction, makes a case for aligning assessments with state and district curriculum frameworks and examines ways in which states have shifted their curriculum frameworks and related state assessment programs to reflect the NCTM Standards and other perspectives. The third booklet, Keeping Score, discusses issues to be considered while developing high quality mathematics assessments. This series is specifically designed to be used at the school and school district level by teachers, principals, supervisors, and measurement specialists.
Keywords: Education

Resources for Teaching Middle School Science - Institute of Medicine; National Academy of Engineering (The National Academies Press, 1998)
With age-appropriate, inquiry-centered curriculum materials and sound teaching practices, middle school science can capture the interest and energy of adolescent students and expand their understanding of the world around them. Resources for Teaching Middle School Science, developed by the National Science Resources Center (NSRC), is a valuable tool for identifying and selecting effective science curriculum materials that will engage students in grades 6 through 8. The volume describes more than 400 curriculum titles that are aligned with the National Science Education Standards. This completely new guide follows on the success of Resources for Teaching Elementary School Science, the first in the NSRC series of annotated guides to hands-on, inquiry-centered curriculum materials and other resources for science teachers. The curriculum materials in the new guide are grouped in five chapters by scientific area—Physical Science, Life Science, Environmental Science, Earth and Space Science, and Multidisciplinary and Applied Science. They are also grouped by type—core materials, supplementary units, and science activity books. Each annotation of curriculum material includes a recommended grade level, a description of the activities involved and of what students can be expected to learn, a list of accompanying materials, a reading level, and ordering information. The curriculum materials included in this book were selected by panels of teachers and scientists using evaluation criteria developed for the guide. The criteria reflect and incorporate goals and principles of the National Science Education Standards. The annotations designate the specific content standards on which these curriculum pieces focus. In addition to the curriculum chapters, the guide contains six chapters of diverse resources that are directly relevant to middle school science. Among these is a chapter on educational software and multimedia programs, chapters on books about science and teaching, directories and guides to science trade books, and periodicals for teachers and students. Another section features institutional resources. One chapter lists about 600 science centers, museums, and zoos where teachers can take middle school students for interactive science experiences. Another chapter describes nearly 140 professional associations and U.S. government agencies that offer resources and assistance. Authoritative, extensive, and thoroughly indexed—and the only guide of its kind—Resources for Teaching Middle School Science will be the most used book on the shelf for science teachers, school administrators, teacher trainers, science curriculum specialists, advocates of hands-on science teaching, and concerned parents.
Keywords: Education

Observations on the President's Fiscal Year 1999 Federal Science and Technology Budget - Institute of Medicine; National Academy of Sciences; National Academy of Engineering (The National Academies Press, 1998)
In this report, the Committee on Science, Engineering, and Public Policy (COSEPUP) provides its observations on the federal science and technology (FS&T) portion of the president's fiscal year (FY) 1999 submission. The FS&T budget (see box) reflects the federal investment in the creation of new knowledge and technologies and excludes such activities as the testing and evaluating of new weapons systems.
Keywords: Policy for Science and Technology; Education

International Benchmarking of US Materials Science and Engineering Research (The National Academies Press, 1998)
Keywords: Engineering and Technology

Assessing the Value of Research in the Chemical Sciences - National Research Council (The National Academies Press, 1998)
This book captures the messages from a workshop that brought together research managers from government, industry, and academia to review and discuss the mechanisms that have been proposed or used to assess the value of chemical research. The workshop focused on the assessment procedures that have been or will be established within the various organizations that carry out or fund research activities, with particular attention to the Government Performance and Results Act (GPRA). The book presents approaches and ideas from leaders in each area that were intended to identify new and useful ways of assessing the value and potential impact of research activities.
Keywords: Math, Chemistry, and Physics

Supporting Research and Data Analysis in NASA's Science Programs: Engines for Innovation and Synthesis - National Research Council (The National Academies Press, 1998)
Effective science, clearly a mandate for the National Aeronautics and Space Administration (NASA), involves asking significant questions about the physical and biological world and seeking definitive answers. Its product is new knowledge that has value to the nation. NASA's flight projects are highly visible and usually the most costly elements of this process, but they are only a part of the science enterprise. Flight projects are founded on research that defines clear scientific goals and questions, designs missions to address those questions, and develops the required technologies to accomplish the missions. This research is funded primarily by NASA's research and analysis (R&A) programs. Data from flight projects are transformed into knowledge through analysis and synthesis-research that is funded both by R&A and by the data analysis (DA) portion of mission operations and data analysis (MO&DA) programs. R&A and DA programs are the subject of this report and are grouped for convenience under the heading of research and data analysis (R&DA).
Keywords: Space and Aeronautics

Review of the Prince William Sound, Alaska, Risk Assessment Study (The National Academies Press, 1998)
Keywords: Earth Sciences; Environment and Environmental Studies

Investing in Research Infrastructure in the Behavioral and Social Sciences - National Research Council (The National Academies Press, 1998)
Keywords: Behavioral and Social Sciences; Policy for Science and Technology

Partners on the Frontier: The Future of U.S.-Russian Cooperation in Science and Technology - National Research Council (The National Academies Press, 1998)
Keywords: Policy for Science and Technology; Biology and Life Sciences

Global Economy, Global Technology, Global Corporations: Reports of a Joint Task Force of the National Research Council and the Japan Society for the Promotion of Science on the Rights and Responsibilities of Multinational Corporations in an Age of Technological Interdependence - National Research Council (The National Academies Press, 1998)
Keywords: Industry and Labor; Engineering and Technology

Developing a Digital National Library for Undergraduate Science, Mathematics, Engineering and Technology Education: Report of a Workshop - National Research Council (The National Academies Press, 1998)
In 1996, the National Science Foundation (NSF) released a report about ways to improve undergraduate science, mathematics, engineering, and technology (SME&T) education. One recommendation called for establishing a digital library, similar to those that are being constructed for many research communities, that would make available electronically a wide variety of materials for improving teaching and learning of SME&T. The NSF asked the National Research Council to examine the feasibility of and issues associated with establishing such a digital national library. In response, an NRC steering committee commissioned a series of papers and convened a workshop to consider these issues. This resulting book delineates the issues that should be considered and provides recommendations to resolve them prior to committing funds.
Keywords: Education; Behavioral and Social Sciences

U.S.-European Collaboration in Space Science - National Research Council (The National Academies Press, 1998)
U.S.-European Collaboration in Space Science reviews the past 30 years of space-based research across the Atlantic. The book, which was prepared jointly with the European Space Science Committee (under the aegis of the European Science Foundation) begins with a broad survey of the historical and political context of U.S.-European cooperation and collaboration in space. The focus of the book is a set of 13 U.S.-European missions in astrophysics, space physics, planetary sciences, earth sciences, and life and microgravity research that illustrate "lessons learned" on the evolution of the cooperation, mission planning and scheduling, international agreements, cost-sharing, management, and scientific output. These lessons form the basis of the joint committee's findings and recommendations, which serve to improve the future conduct and enhance the scientific output of U.S.-European cooperation and collaboration in space science.
Keywords: Space and Aeronautics

Modeling Human and Organizational Behavior: Application to Military Simulations - National Research Council (The National Academies Press, 1998)
Simulations are widely used in the military for training personnel, analyzing proposed equipment, and rehearsing missions, and these simulations need realistic models of human behavior. This book draws together a wide variety of theoretical and applied research in human behavior modeling that can be considered for use in those simulations. It covers behavior at the individual, unit, and command level. At the individual soldier level, the topics covered include attention, learning, memory, decisionmaking, perception, situation awareness, and planning. At the unit level, the focus is on command and control. The book provides short-, medium-, and long-term goals for research and development of more realistic models of human behavior.
Keywords: Conflict and Security Issues; Behavioral and Social Sciences

Trends in the Early Careers of Life Scientists - National Research Council (The National Academies Press, 1998)
In each year between 1994 and 1996, more than 7,000 individuals received a Ph.D. in life-science, and the number of graduates is rising sharply. If present trends continue, about half of those graduates will have found permanent positions as independent researchers within ten years after graduation. These statistics—and the labor market situation they reflect—can be viewed either positively or negatively depending on whether one is a young scientist seeking a career or an established investigator whose productivity depends on the labor provided by an abundant number of graduate students. This book examines the data concerning the production of doctorates in life-science and the changes in the kinds of positions graduates have obtained. It discusses the impact of those changes and suggests ways to deal with the challenges of supply versus demand for life-science Ph.D. graduates. Trends in the Early Careers of Life Scientists will serve as an information resource for young scientists deciding on career paths and as a basis for discussion by educators and policymakers as they examine the current system of education linked to research and decide if changes in that system are needed.
Keywords: Policy for Science and Technology; Industry and Labor

High School Mathematics at Work: Essays and Examples for the Education of All Students - National Research Council (The National Academies Press, 1998)
Traditionally, vocational mathematics and precollege mathematics have been separate in schools. But the technological world in which today's students will work and live calls for increasing connection between mathematics and its applications. Workplace-based mathematics may be good mathematics for everyone. High School Mathematics at Work illuminates the interplay between technical and academic mathematics. This collection of thought-provoking essays—by mathematicians, educators, and other experts—is enhanced with illustrative tasks from workplace and everyday contexts that suggest ways to strengthen high school mathematical education. This important book addresses how to make mathematical education of all students meaningful—how to meet the practical needs of students entering the work force after high school as well as the needs of students going on to postsecondary education. The short readable essays frame basic issues, provide background, and suggest alternatives to the traditional separation between technical and academic mathematics. They are accompanied by intriguing multipart problems that illustrate how deep mathematics functions in everyday settings—from analysis of ambulance response times to energy utilization, from buying a used car to "rounding off" to simplify problems. The book addresses the role of standards in mathematics education, discussing issues such as finding common ground between science and mathematics education standards, improving the articulation from school to work, and comparing SAT results across settings. Experts discuss how to develop curricula so that students learn to solve problems they are likely to encounter in life—while also providing them with approaches to unfamiliar problems. The book also addresses how teachers can help prepare students for postsecondary education. For teacher education the book explores the changing nature of pedagogy and new approaches to teacher development. What kind of teaching will allow mathematics to be a guide rather than a gatekeeper to many career paths? Essays discuss pedagogical implication in problem-centered teaching, the role of complex mathematical tasks in teacher education, and the idea of making open-ended tasks—and the student work they elicit—central to professional discourse. High School Mathematics at Work presents thoughtful views from experts. It identifies rich possibilities for teaching mathematics and preparing students for the technological challenges of the future. This book will inform and inspire teachers, teacher educators, curriculum developers, and others involved in improving mathematics education and the capabilities of tomorrow's work force.
Keywords: Education

Agriculture's Role in K-12 Education: Proceedings of a Forum on the National Science Education Standards - National Research Council (The National Academies Press, 1998)
Keywords: Agriculture; Education

Nobel Prize Women in Science: Their Lives, Struggles, and Momentous Discoveries: Second Edition - Sharon Bertsch McGrayne (The National Academies Press, 1998)
Since 1901 there have been over three hundred recipients of the Nobel Prize in the sciences. Only ten of them—about 3 percent—have been women. Why? In this updated version of Nobel Prize Women in Science, Sharon Bertsch McGrayne explores the reasons for this astonishing disparity by examining the lives and achievements of fifteen women scientists who either won a Nobel Prize or played a crucial role in a Nobel Prize - winning project. The book reveals the relentless discrimination these women faced both as students and as researchers. Their success was due to the fact that they were passionately in love with science. The book begins with Marie Curie, the first woman to win the Nobel Prize in physics. Readers are then introduced to Christiane Nusslein-Volhard, Emmy Noether, Lise Meitner, Barbara McClintock, Chien-Shiung Wu, and Rosalind Franklin. These and other remarkable women portrayed here struggled against gender discrimination, raised families, and became political and religious leaders. They were mountain climbers, musicians, seamstresses, and gourmet cooks. Above all, they were strong, joyful women in love with discovery. Nobel Prize Women in Science is a startling and revealing look into the history of science and the critical and inspiring role that women have played in the drama of scientific progress.
Keywords: Explore Science; Biography and Autobiography

(NAS Colloquium) Neuroimaging of Human Brain Function (The National Academies Press, 1998)
The colloquium on "Imaging of Cognitive Function" speaks to the many audiences whose interests relate to efforts to map cognitive processes in the human brain. There are things of great interest in this collection of papers for specialists in cognition and neuroscience and imaging science as well as in disciplines interested in human development through education and training and others with intrinsic interest in the latest information on how the human brain supports thought. The papers were presented at a meeting sponsored by the National Academy of Sciences in its western home the Beckman Center at the University of California, Irvine.
Keywords: Health and Medicine; Biology and Life Sciences